Estimating the effect of being close to outdoor activities on cottage prices: The case of Northern Finland before and after Covid-19 - Elovirta, Salla (My University, 2022)
In the beginning of 2020, a global pandemic Covid-19 spread around the world, affecting people’s lives in multiple ways. In addition, many of the global and local markets were impacted, for example the real estate markets. In this thesis the changes the cottage real estate markets of Northern Finland have experienced are examined by looking at cottage prices per square meter before and after the pandemic. Northern Finland is defined as the entire area of Lapland and the municipalities of Kuusamo and Pudasjärvi. Nature is abundant in Northern Finland and urban areas are scarce, and most of the popular activities are outdoor activities: in winter downhill skiing and Nordic skiing and in summer hiking and mountain biking. The purpose of this thesis is to look into if in Northern Finland Covid-19 has impacted the price per square meter of cottages near Nordic skiing, hiking and mountain biking -tracks differently than of cottages near downhill skiing locations. The topic of cottages, which are sometimes also called second homes or free-time residences, and especially cottage prices has not been widely researched in the past, and seemingly not at all in Northern Finland. This thesis aims to add to the topic of cottage real estate prices and to start the research on the topic in Northern Finland. Difference-in-Difference analysis is used as the analysis method, to find if there have been differences in reactions to Covid-19 between cottages in different locations. The model created derives also from the theory of hedonic price model, as a basis for how to estimate the effect on price of attributes external to the properties. For the analysis data on cottage sales in Northern Finland from 2017 to 2021 was received from the Federation of real estate agency in Finland. It was found that in answer to the research question, the connection between Covid-19 and cottage price per square meter seems to be heterogeneous based on how close to it is to which outdoor activities. Being near downhill skiing activities seems be associated with higher cottage price per square meter, and the price would seem to increase even more when the cottage is near both downhill and Nordic skiing. This was found to apply both before and after Covid-19, but the estimates increased significantly after Covid-19. The estimates for being only near Nordic skiing were found not to be statistically significant post-pandemic, but there is an indication that being only near Nordic skiing is associated with slightly lower cottage prices after Covid-19. Indications were also found that there are differences between different areas in the connection between price per square meter and cottage location in relation to outdoor activities.

Vuoden 2020 alussa maailmanlaajuinen pandemia Covid-19 levisi ympäri maailman, vaikuttaen ihmisten elämään monin eri tavoin. Samoin pandemia vaikutti eri markkinoihin, esimerkiksi kiinteistömarkkinoihin. Tässä tutkielmassa tutkitaan millaisia muutoksia pohjoisen Suomen asuntomarkkinat ovat kokeneet, tarkastelemalla mökkien neliöhintoja ennen ja jälkeen pandemian. Tutkielmassa määritelmä pohjoinen Suomi sisältää koko Lapin alueen, sekä Kuusamon ja Pudasjärven kunnat. Luonto on tarjolla ja saatavilla suurissa määrissä pohjoisessa Suomessa, ja suurin osa suosituista aktiviteeteista ovat ulkoilma-aktiviteetteja: talvella laskettelu ja murtomaahiihto, ja kesällä vaeltaminen ja maastopyöräily. Tämän tutkielman tarkoituksena on selvittää, onko Covid-19 vaikuttanut pohjoisessa Suomessa eri tavoin mökkien neliöhintoihin, riippuen siitä onko mökki lähellä lasketteluaktiviteetteja vai murtomaahiihtoa. Mökkien, tai vapaa-ajan asuntojen, hintoja ei ole aikaisemmin tutkittu paljoa, etenkään pohjoisen Suomen aluerajauksella tehtyjä tutkimuksia ei löydy. Tämän tutkielman tavoitteena on myös jatkaa mökkejä ja niiden hintoja koskevaa tutkimusta, sekä aloittaa mökkien hintojen tutkiminen pohjoisessa Suomessa. Analyysimenetelmänä käytetään Difference-in-Difference analyysiä, eri aktiviteettien läheisyydessä olevien mökkien neliöhintojen muutosten eroavaisuuksien tarkasteluun. Käytetty malli pohjaa myös hedonisen hintamallin teoriaan mökkien itsensä ulkopuolisten ominaisuuksien, sijainnin, vaikutuksen neliöhintaan arvioimiseksi. Analyysia varten käytetään Kiinteistönvälittäjien Keskusliitolta saatua data pohjoisessa Suomessa myydyistä mökeistä, vuosien 2017–2021 välillä. Vastauksena tutkimuskysymykseen analyysissa havaittiin, että Covid-19:ta yhteys eri sijainneilla olevien mökkien neliöhintoihin vaikuttaisi olevan heterogeeninen. Lasketteluhissien läheisellä sijainnilla vaikuttaisi olevan yhteys korkeampiin mökkihintoihin, etenkin jos mökki on lähellä sekä lasketteluhissejä että hiihtolatuja. Tämän havaittiin pitävän paikkansa sekä ennen että jälkeen pandemian, joskin pandemian jälkeen estimaatit kasvoivat merkittävästi. Estimaatit hiihtolatujen läheisyydelle lasketteluhissien ollessa kaukana eivät olleet pandemian jälkeiselle ajalle tieteellisesti merkitseviä. Mutta vaikuttaisi siltä, että pandemian jälkeen vain hiihtolatujen läheisyydessä sijaitsevat mökit ovat yhteydessä matalampiin neliöhintoihin kuin ennen pandemiaa. Tutkimuksessa havaittiin myös, että eri alueiden välillä saattaa olla eroja ulkoilma-aktiviteettien ja mökin hinnan välisessä yhteydessä.
Keywords: cottages, second home, real estate market, Covid-19, pandemic, difference-in-difference